2015
DOI: 10.1145/2699266
|View full text |Cite
|
Sign up to set email alerts
|

Depth Artifacts Caused by Spatial Interlacing in Stereoscopic 3D Displays

Abstract: Most spatially interlacing stereoscopic 3D displays display odd and even rows of an image to either the left or right eye of the viewer. The visual system then fuses the interlaced image into a single percept. This row-based interlacing creates a small vertical disparity between the images; however, interlacing may also induce horizontal disparities, thus generating depth artifacts. Whether people perceive the depth artifacts, and if so, what is the magnitude of the artifacts, are unknown. In this study, we hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Thus, depth distortions due to the vertical offsets in spatial-interlacing displays should not occur with this technique. We did not test this possibility because Hakala et al [3] have already shown that this type of distortion occurs with spatial interlacing and there is no reason to believe that it should occur with the hybrid protocols proposed here.…”
Section: Experiments 4: Depth Distortionmentioning
confidence: 95%
See 3 more Smart Citations
“…Thus, depth distortions due to the vertical offsets in spatial-interlacing displays should not occur with this technique. We did not test this possibility because Hakala et al [3] have already shown that this type of distortion occurs with spatial interlacing and there is no reason to believe that it should occur with the hybrid protocols proposed here.…”
Section: Experiments 4: Depth Distortionmentioning
confidence: 95%
“…Because the left-and right-eye views are offset vertically by one pixel, the eyes make a vertical vergence eye movement to binocularly fuse the rows (bright rows aligned in the two eyes and dark rows also aligned). The vertical eye movement causes a change in the horizontal disparity at the retinas for off-vertical and off-horizontal edges, so those edges appear at unintended depths [3]. Interestingly, some spatial-interlacing displays eliminate this effect by presenting data rows alternately [23,24].…”
Section: Experiments 4: Depth Distortionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hakala et al measured how spatial interlacing affects depth distortion [13]. The stimulus was an edge between the white and black regions.…”
Section: Spatial Interlacingmentioning
confidence: 99%